Pengaruh Kompetensi, Komitmen Organisasi Dan Motivasi Terhadap Kinerja Pegawai Badan Kesatuan Bangsa Dan Politik Kabupaten Penajam Paser Utara - Ilham; Hamid, Mulyadi; Rukaiyah, St (STIM-LPI Makassar, 2024)
This research aims to determine and analyze the influence of Competence, Organizational Commitment and motivation on Employee Performance at the National Unity and Political Agency of North Penajam Paser Regency partially and jointly. The research method used is quantitative descriptive research using Multiple Linear Regression data analysis using SPSS software. Primary data was obtained from respondents, namely employees of the National Unity and Politics Agency for North Penajam Paser Regency. The population was 45 ASN and the sampling technique used was saturated sampling, meaning the entire population was sampled in this study. The results of the research show that partially there is a positive influence between Competence, Organizational Commitment and Motivation on the Performance of Employees of the National Unity and Political Agency of North Penajam Paser Regency. Together, there is also a positive influence between Competence, Organizational Commitment and motivation on the Performance of Employees of the National Unity and Political Agency of North Penajam Paser Regency.